Enhancement of thermal and mechanical properties of silicone rubber with γ-ray irradiation-induced polysilane-modified graphene oxide/carbon nanotube hybrid fillers. Issue 53 (12th October 2021) - Cao, Ke; Li, Bolong; Jiao, Yang; Lu, Yongjun; Wang, Liancai; Guo, Yueying; Dai, Pei
Abstract : In this work, functionalized silicon rubber with hybrid nanocarbon filler was prepared. The composites with good resistance ability to stress relaxation can be used as underfill to improve the thermo-mechanical reliability of flip-chips. Abstract : In this study, a polysilane-modified graphene oxide (GO) and carbon nanotube (CNT) nanocomposite (GO/CNTs-Si) was prepared as a thermal conductive nanofiller to enhance the thermal and mechanical properties of silicone rubber composites. By γ-ray-radiation 3-methacryloxypropyltrimethoxy silane (MPTMS) was polymerized on the surface of GO and CNTs to improve the interfacial interaction between the GO/CNTs-Si and SR matrix. FTIR characterization results demonstrated that polysilane modified the GO/CNTs successfully. The pristine GO/CNTs and resultant GO/CNTs-Si were individually incorporated into α, ω-dihydroxypolydimethylsiloxane to vulcanize SR composites. Compared with SR–GO/CNTs, SR–GO/CNT-Si exhibited better mechanical and thermal performance. Moreover, the time-dependent complex modulus of SR–GO/CNTs-Si was much higher than that of SR–GO/CNTs, which indicates longer service time and more stable performance. In terms of electronic packaging, SR–GO/CNTs exhibited better performance than the 1180B counterpart. The low value of warpage of chip packaged by SR–GO/CNTs implied that SR–GO/CNTs-Si could have potential application as the thermal interface electronic packaging material.